PENGARUH BAURAN PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PRINCIPAL MENGGUNAKAN PRODUK SURETY BOND DI PT. JAMKRIDA SUMSEL - Ardian Yurdianto; Fakhry Zamzam; Luis Marnisah (Journal of Global Business and Management Review, 2020)
This study entitled The Effect of Promotion Mix and Service Quality on Principal Decisions Using Surety Bond Products at PT Jamkrida Sumsel. This research instrument uses a questionnaire, and using multiple linear regression to process tabulated data from the results of respondents' answers. The results of the study conclude, First, the Promotion Mix Variable (X1) has a positive and significant effect on the Decision of Jamkrida Service Users in South Sumatra (Y;. Second, the Service Quality Variable (X2) has a positive and significant effect on the Decision of South Sumatra Jamkrida Service Users (Y); Third, Promotion Mix Variable (X1) is an independent variable whose influence is more dominant on the Decision of Jamkrida Service Users in South Sumatra compared to the variable of service quality; Fourth, the Promotion Mix variable (X1) and Service Quality (X2) have a positive and significant effect on the Decision of Jamkrida Service Users in South Sumatra (Y). This means that the independent variable (X) is increasing together, so the Decision of the Jamkrida Service User of South Sumatra (Y) will increase.